499 Utilization of Diagnostic Sleep Testing Prior to Idiopathic Hypersomnia Diagnosis Among US Adults: A Real-World Claims Analysis. (3rd May 2021) - Saad, Ragy; Ben-Joseph, Rami; Prince, Patricia; Stack, Catharine; Bujanover, Shay; Taylor, Ben
Abstract: Introduction: A retrospective analysis was conducted to characterize diagnostic sleep testing during the 12 months before diagnosis of idiopathic hypersomnia (IH), a hypersomnolence disorder with no approved treatments. Methods: IBM® MarketScan® claims data were analyzed (1/1/14–9/30/19) to identify adults with newly diagnosed IH, defined as ≥2 claims with an IH diagnosis code ≥1 day and ≤180 days apart, and without an IH diagnosis ≤12 months before cohort entry. Demographics, diagnosing physician specialty, and diagnostic sleep disorder testing (identified via claims with procedure codes for multiple sleep latency test/maintenance of wakefulness test [MSLT/MWT], home sleep test, and polysomnography) were summarized. Analyses were performed on patients with IH diagnosis codes recorded in any position on the claims ("overall IH") and in the primary position ("primary IH") to understand the effects of applying a more specific definition of IH. Results: Of 32, 948, 986 eligible people, 4, 980 (0.015%) newly diagnosed IH patients were identified. Mean age was 43 years and 67% were female; those with primary IH (n=2, 205; 44% of overall IH) were younger (mean age, 39 years) and more likely to be female (73%). Long sleep time was documented for 69% of the overall IH group and 67% of the primary IH group. The top 3 diagnosing physicians' specialties were similar for overall IH/primary IH: pulmonology (23%/26%), neurology (14%/16%), and internal medicine (11%/10%). Few patients (9% overall IH; 7% with primary IH) were diagnosed in family practice. Any sleep testing was performed in 44% of overall IH and 53% of primary IH patients. Polysomnography and MSLT/MWT, the most frequently used sleep tests, were less common in overall IH (39% and 22%) than in primary IH (48% and 32%). Conclusion: IH patients were typically diagnosed by specialists, outside of general medical practice. The most common diagnosing physicians were pulmonologists and neurologists for both the overall and primary IH groups. Objective sleep testing was more frequently documented in diagnosis of primary IH but utilization was low regardless of the definition of IH diagnosis. Further research is needed to investigate the utilization of sleep testing by clinicians for diagnosing IH. Support (if any): Jazz Pharmaceuticals